Application of hydrocarbon and perfluorocarbon oxygen vectors to enhance heterologous production of hyaluronic acid in engineered Bacillus subtilis. Issue 5 (26th February 2018) - Westbrook, Adam W.; Ren, Xiang; Moo‐Young, Murray; Chou, C. Perry
Abstract: In microbial cultivations for hyaluronic acid (HA) production, oxygen can be a limiting substrate due to its poor solubility in aqueous medium and the substantial increase in culture viscosity at relatively low HA titers. Shear stress due to the high agitation and aeration rates required to overcome oxygen limitation may reduce the quality (i.e., molecular weight) of HA, and production costs associated with power consumption and supplemental oxygen may be excessive. Here, we report the application of oxygen vectors to the heterologous production of HA in engineered Bacillus subtilis, leading to significantly improved culture performance. We first derived an improved HA‐producing strain of B. subtilis through engineering of the promoter driving coexpression of seHas and tuaD, leading to high‐level HA production. Out of seven potential oxygen vectors evaluated in a preliminary screening, significant improvements to the HA titer and/or cell density were observed in cultures containing n ‐heptane, n ‐hexadecane, perfluoromethyldecalin, and perfluoro‐1, 3‐dimethylcyclohexane. Adjustments to the vector concentration, timing of vector addition, and the agitation rate resulted in further enhancements, with the HA titer reaching up to 4.5 g/L after only 10 hr cultivation. Moreover, our results indicate that certain vectors may alter the functional expression of Class I hyaluronan synthase (HAS) in B. subtilis, and that higher shear rates may drive more carbon flux through the HA biosynthetic pathway without negatively affecting the MW. Our study demonstrates the efficacy of oxygen vectors to enhance heterologous HA production in B. subtilis, and provides valuable insight for future bioprocess development in microbial HA production. Abstract : Hydrocarbons and perfluorocarbons were evaluated as oxygen vectors to enhance heterologous hyaluronic acid (HA) production in Bacillus subtilis under low‐shear cultivation conditions. Significant improvements to culture performance were observed upon the addition of n‐heptane, n‐hexadecane, perfluoromethyldecalin, and perfluoro‐1, 3‐dimethylcyclohexane, with the HA titer reaching up to 4.5 g/L after only 10 h cultivation. Our results indicate that certain vectors may alter the functional expression of Class I hyaluronan synthase, and higher shear rates are beneficial to HA production in B. subtilis .